Pemodelan Rehabilitasi Sosial pada Pecandu Narkotika - Chaidar, Muhamad; Kusnadi, Sekaring Ayumeida; Alfadani, Ahmad Zakariyah; Lystiadi, Intan Predita (Universitas Muhammadiyah Ponorogo, 2025)
The abuse of narcotics in Indonesia has become a serious social issue, which not only impacts individual health but also creates widespread social and economic disturbances. One of the solutions implemented to address this problem is social rehabilitation for drug addicts, aimed at reintegrating individuals into positive and productive social roles. This article discusses the modeling of social rehabilitation for drug addicts from a legal perspective, referring to Law Number 35 of 2009 concerning Narcotics, which regulates the provision of rehabilitation as an alternative to punishment for drug users. The social rehabilitation model involves several stages, including assessment, medical and psychosocial rehabilitation, and social reintegration into the community. Additionally, the legal approach applied must prioritize the principles of restorative justice, aimed at restoring relationships between addicts, the community, and victims, as well as reducing the negative stigma against addicts. However, the implementation of social rehabilitation also faces challenges, such as social stigma, limited resources, and ineffective coordination among law enforcement agencies, rehabilitation institutions, and the community. This article concludes that a social rehabilitation model based on human rights principles, restorative justice, and comprehensive support from various parties can accelerate the recovery of drug addicts and facilitate their reintegration back into society.